PERBANDINGAN PERAN SUMBER PERMODALAN SEBAGAI PENGUATAN USAHA MIKRO KECIL MENENGAH (UMKM) SEBELUM DAN SELAMA COVID-19 (2018 S.D 2021) - Anggi Prastyono; Nasutra (Halu Oleo University, 2024)
The Micro, Small, and Medium Enterprises (MSMEs) have become one of Indonesia's economic sectors affected by Covid-19. The capital sources for MSMEs before and during COVID-19 (2018 to 2021) have presented two distinct situations, which we address in this study. The research aims to analyze the differing situations regarding the primary capital sources for MSMEs before and during COVID-19 (2018 to 2021). The research methodology involves a qualitative literature review utilizing data from articles on Google Scholar between 2018 and 2021 using the keyword